2022
DOI: 10.1002/jat.4410
|View full text |Cite
|
Sign up to set email alerts
|

Obeticholic acid improved triptolide/lipopolysaccharide‐induced hepatotoxicity by inhibiting caspase‐11‐GSDMD pyroptosis pathway

Abstract: This study was designed to investigate the potential role of farnesoid X receptor (FXR) in abnormal bile acid metabolism and pyroptosis during the pathogenesis of triptolide (TP)/lipopolysaccharide (LPS)-induced hepatotoxicity. Moreover, the protective effect of obeticholic acid (OCA) was explored under this condition. In vivo, female C57BL/6 mice were administrated with OCA (40 mg/kg bw, intragastrical injection) before (500 μg/kg bw, intragastrical injection)/LPS (0.1 mg/kg bw, intraperitoneal injection) adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…TNF-R1, which is expressed on almost every mammalian cell type, including hepatocytes, regulates a number of biological responses, ranging from NF-κB activation to cell death, when it is activated by TNF-α. Previously, we confirmed that decreased TNF-α levels exogenously administered or facilitated by LPS might counteract TP-induced hepatotoxic reactions, especially apoptosis and necroptosis, in vivo and in vitro . To maintain the consistency of the experimental conditions, TNF-α was used instead of LPS as a stimulus for in vitro experiments.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…TNF-R1, which is expressed on almost every mammalian cell type, including hepatocytes, regulates a number of biological responses, ranging from NF-κB activation to cell death, when it is activated by TNF-α. Previously, we confirmed that decreased TNF-α levels exogenously administered or facilitated by LPS might counteract TP-induced hepatotoxic reactions, especially apoptosis and necroptosis, in vivo and in vitro . To maintain the consistency of the experimental conditions, TNF-α was used instead of LPS as a stimulus for in vitro experiments.…”
Section: Discussionmentioning
confidence: 65%
“…Thus, we selected LPS as a stimulant and found that TP/LPS cotreatment caused severe liver injury and massive hepatic cell death. 44,45 As Tolllike receptor 4 (TLR-4) is expressed at low levels in hepatocytes, it is not suitable to use LPS as a direct stimulant for in vitro hepatocyte experiments. However, TNF-α is a pro-inflammatory factor produced by LPS-activated immune cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations